Reports of Charity Organisation Committee of the Statistical and Social Inquiry Society of Ireland, appointed 7th December, 1875 - SSISI (Statistical and Social Inquiry Society of Ireland, 1876)
The committee was appointed at the December meeting of the Council, to consider and make suggestions upon the subject of a charity organisation: (1) To collect further information as to the working of charity organisation in London, New York, Elberfeld, and other places; (2) To collect information as to the working of charities in Dublin, and to suggest the branches of Charity organisation that could be best undertaken by charitable bodies in Dublin; (3) To collect, through existing charitable organisations, information as to the causes of pauperism, and to suggest means by which such information may be more completely and systematically collected
Twenty ninth session ? 1875/1876
Keywords: Pauperism; Poverty; charity organisations; 314.15